Evaluation of awareness and importance of child vaccination among mothers carrying children of age 1 to 4 years in Lyari, Karachi, Pakistan - Siddiqui, Nausheen Hameed; Yousaf, Shanza; Saeed, Javaria; Wahid , Shahana; Abdul Khaliq, Sheikh; Ahmed, Imran (International Journal of Pathology, 2026)
Background: Despite attempts to promote immunization, Pakistan’s suboptimal child vaccination rates lead to avoidable diseases and high infant mortality, demanding a better understanding of mothers’ vaccination knowledge. The current study aimed to assess the level of awareness and knowledge regarding childhood vaccination among mothers and examine its association with demographic characteristics. Methods: A cross-sectional survey was conducted among 250 mothers using a structured validated questionnaire. The data collected included demographic information, knowledge of vaccine benefits, and perceptions of vaccination schedules. The association between awareness and chosen factors were evaluated statistically using Chi-square. Results: The 67.2% respondents, demonstrated awareness about vaccination. Significant associations were observed between vaccination awareness and educational level (p=0.0001), number of children (p=0.004), and age of the youngest child (p=0.002). Mothers who acknowledged the benefits of vaccination and the role of vaccines in preventing diseases were significantly more likely to have vaccinated their children (p<0.001). However, gaps remained in knowledge related to vaccine schedules, misconceptions about vaccination during illness, and the belief that one vaccine can immunize against all diseases. Conclusion: Our findings emphasize the necessity for targeted health education programs to upgrade maternal knowledge and correct misconceptions about childhood immunization. Community-based interventions including healthcare professionals, media, and local influencers are advised to increase vaccine uptake and achieve complete vaccination coverage. ‎